Water supply in the critical period of maize and the grain production - Bergamaschi, Homero; Dalmago, Genei Antonio; Bergonci, João Ito; Bianchi, Cleusa Adriane Menegassi; Müller, Artur Gustavo; Comiran, Flávia; Heckler, Bruna Maria Machado (Pesquisa Agropecuaria Brasileira, 2004)
Maize crops may experience reductions of grain yields when submitted to water deficit during the critical period of crop cycle, from tasseling stage to beginning of grain filling. The objective of this work was to demonstrate the importance of the water supply during the critical period on the grain production of maize. Experiments were conducted in Eldorado do Sul, Brazil (30°5'S; 51°40'W; 40 m altitude), during the crop seasons of 1998/1999 and 2002/2003, characterized by La Niña and El Niño phenomenon, respectively. Data of grain yield and its components were obtained in field experiments, using different volumes of water applied through irrigation. The grain yields showed an opposite tendency when compared to the regional estimated average. In 1998/1999, during a long drought period, 46.8 mm of rain on the critical period allowed a grain yield of about 8 t ha-1 without irrigation. In contrast, in 2002/2003 a short drought during the critical period reduced the grain yield to less than 2 t ha-1, affecting the number of ear per plant and the number of kernel per ear. Therefore, risks in the expected maize production are probable, although having climatic forecasting of favorable rain distribution in the region, such as by El Niño phenomenon.
Keywords: water deficit; irrigation; yield components; climatic risk